PEMANFAATAN RHIZOBAKTERI PELARUT FOSFAT DARI TANAMAN LEGUM UNTUK PENINGKATAN PERTUMBUHAN DAN HASIL TANAMAN KEDELAI - Budiyani, Ni Komang; Wirya, G. N. Alit Susanta; Sudana, I Made; Raka, I Gusti Ngurah (Journal of Agricultural Science and Biotechnology; Vol 7 No 1 (2018), 2018)
Soybean is one of the strategic commodities in Indonesia. Soybean became the third most important crop after rice and maize. Leguminose plants are known to have microbial diversity in soils through their root exudates and can have a positive impact on plant growth. The use of rhizobacteria, known as Plant Growth Promoting Rhizobacteria (PGPR), is a bacteria that lives in the root area (rhizospher) and plays an important role in the growth of plants with the ability to form colonies around the roots quickly and can maintain environmental sustainability, one of bacteria rootsis phosphate solubilizing bacteria. This research is conducted to determine the influence of phosphate solubilizing bacteria on the growth and yield of soybean crops. This study used a factorial pattern (RAK) with 3 repetition and 9 treatments. Treatments of Rhizo 09 isolates from undis Rhizosfer here showed the best results.The analysis of sequencing and pyhlogeni shows that Rhizo 09 has close proximity withFlavobakterium johnsoniae from China and having a high similarity (98%) and a small genetic distance (0.003).